INDUKSI PADA PASIEN PEB DENGAN KARDIOMIOPATI DAN EDEMA PARU - Suryani, Shila; Prihatno, MM Rudi (MANDALA of Health, 2014)
Preeclampsi is a desease that occur in pragnancy after 20 weeks gestaton with manifestation include multiorgans system such as pulmonary oedema and ventricel disfunction. Cardiomyopathy is a heart disorder that characterized by myocard disfunction and there is no relation with others heart desease before.            This case report discuss about induction anesthesia management to a women, 22 years old diagnosed with GIP0A0, severe preeclampsi, pulmonary oedem, cardiomyopathy, and fetal distress underwent caesaria section. Its a challange for anesthesiologist, how anesthesia management to this patient. There are four thing that we should do when induction, that is : optimalitation of preoxygenation,  give positive pressure ventilation with PEEP, minimal myocardial depressant effect of drugs, and keep normovolume. By doing these things we can keep adequate oxygenation so that can increase mother and baby outcome